2013
DOI: 10.1093/mnras/stt2001
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and feedback in the inner kiloparsec of the active galaxy NGC 2110

Abstract: We present two-dimensional gaseous kinematics of the inner 1.1 × 1.6 kpc 2 of the Seyfert 2 galaxy NGC 2110, from optical spectra (5600-7000Å) obtained with the GMOS integral field spectrograph on the Gemini South telescope at a spatial resolution of ≈ 100 pc. Gas emission is observed over the whole field-of-view, with complex -and frequently double -emissionline profiles. We have identified four components in the emitting gas, according to their velocity dispersion (σ), which we refer to as: (1) warm gas disk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 41 publications
5
32
0
1
Order By: Relevance
“…Our galaxies span a wide range of AGN bolometric luminosities, overlapping with low-luminosity local Seyfert galaxies (e.g., Müller-Sánchez et al 2011;Schnorr-Müller et al 2014) as well as high-luminosity quasars (e.g., Liu et al 2013a;Mcelroy et al 2015). The average mass outflow rate for the 18 galaxies modeled in this work is ∼10 2.7 M yr −1 .…”
Section: The Biconical Outflows In This Sample Are Largementioning
confidence: 77%
“…Our galaxies span a wide range of AGN bolometric luminosities, overlapping with low-luminosity local Seyfert galaxies (e.g., Müller-Sánchez et al 2011;Schnorr-Müller et al 2014) as well as high-luminosity quasars (e.g., Liu et al 2013a;Mcelroy et al 2015). The average mass outflow rate for the 18 galaxies modeled in this work is ∼10 2.7 M yr −1 .…”
Section: The Biconical Outflows In This Sample Are Largementioning
confidence: 77%
“…We typically use the maximum velocity and velocity dispersion reported in the respective papers. For studies using different emission lines (i.e., Schnorr-Müller et al 2016;Riffel et al 2015;Schönell et al 2014;Schnorr-Müller et al 2014;Riffel et al 2013;Riffel & Storchi-Bergmann 2011b,a;Müller-Sánchez et al 2011;Storchi-Bergmann et al 2010), we adopt the values of mass outflow rates reported in the respective papers. We underline here that by adopting the simplest prescription for the calculation of the mass outflow rate and due to the effects discussed above, the values shown in Fig.…”
Section: Mass Outflow Ratesmentioning
confidence: 99%
“…This relationship between the observed line-emitting gas mass, n e and L Hβ (or an equivalent using L Hα ) is commonly adopted in studies of outflows (e.g., Holt et al 2006;Genzel et al 2011;Rodríguez Zaurín et al 2013;Liu et al 2013b;Schnorr-Müller et al 2014) with normalisation factors that vary within a factor of a few, depending on the exact assumptions. Using our extinction un-corrected L Hβ values (Table 4.2), we obtain total observed ionised gas masses of M gas = (2-40) ×10 7 M ⊙ , assuming the commonly adopted n e = 100 cm −3 (e.g., Liu et al 2013b), or M gas = (0.4-8) ×10 7 M ⊙ assuming our median value of n e = 500 cm −3 .…”
Section: Outflow Properties: Estimates Of Mass Energy and Momentummentioning
confidence: 99%